An investigation of attitudes towards tax evasion and welfare fraud in New Zealand. Issue 1 (March 2017) - Marriott, Lisa
This study undertakes an empirical exploration of attitudes towards tax evasion and welfare fraud in New Zealand. Prior research indicates that society has different attitudes towards these two crimes. However, it is not known why this is the case, particularly as both crimes are conceptually similar. The study has two aims. The first is to measure the extent to which society views tax evasion and welfare fraud differently in New Zealand. The second, and primary, objective of this research is to offer an explanation for why different views exist. The dual-process model, using social dominance orientation and right-wing authoritarianism is used for analytical purposes. Responses from 1500 survey participants show that New Zealanders do have different attitudes towards welfare fraud and tax evasion. In contrast to previous research findings, this study shows that harsher attitudes are held towards tax evasion than welfare fraud. Education and income level provide the greatest level of significance in explaining attitudes towards welfare fraud; and age and income source provide the greatest level of significance in explaining attitudes towards tax evasion.